Breastfeeding promotion and counseling training effect on the skills posyandu cadre as stunting prevention - Listiyanawati, Mutiara Dewi; Maretta, Megayana Yessy; Susilaningsih, Endang Zulaicha; Sensussiana, Titis; Vioneery, Deoni; Prastiwi, Firman (MEDIA ILMU KESEHATAN, 2024)
Background: Improving the quality of human life should commence right from infancy. One pivotal factor contributing to this enhancement is breastfeeding (or breast milk). Challenges concerning the limited coverage of exclusive breastfeeding persist due to insufficient empowerment and suboptimal education activities for breastfeeding counselors, as well as ineffective dissemination, advocacy, and related breastfeeding campaigns. Establishing breastfeeding support groups and cadre is imperative to support mothers in successfully breastfeeding. Objective: The research aimed to assess the impact of Promotion And Breastfeeding Counseling training on cadre’s skills.Methods: This study employed a quasi-experimental design with one group pretest-posttest, utilizing purposive sampling technique. The total sample size consisted of 53 respondents. Test data were analyzed using wilcoxon.Results: The result of the study was known that there was an effect of Promotion And Breastfeeding Counseling training on skills training cadres (0.000 p <0.05). Conclusion: Promotion And Breastfeeding Counseling training effect on the level of skills of cadres.